Monte Carlo simulation of aggregate morphology for simultaneous coagulation and sintering - Schmid, Hans-Joachim; Tejwani, Saurabh; Artelt, Christian; Peukert, Wolfgang (Journal of Nanoparticle Research)
A model for simulation of the three-dimensional morphology of nano-structured aggregates formed by concurrent coagulation and sintering is presented. Diffusion controlled cluster–cluster aggregation is assumed to be the prevailing coagulation mechanism which is implemented using a Monte–Carlo algorithm. Sintering is modeled as a successive overlapping of spherical primary particles, which are allowed to grow as to preserve overall mass. Simulations are characterized by individual ratios τ of characteristic collision to fusion time. A number of resulting aggregate-structures is displayed and reveals structure formation by coagulation and sintering for different values of τ. These aggregates are described qualitatively and quantitatively by their mass fractal dimension Df and radius of gyration. The fractal dimension increases from 1.86 for pure aggregation to ≈ 2.75 for equal characteristic time scales. As sintering turns out to be more and more relevant, increasingly compact aggregates start to form and the radius of gyration decreases significantly. The simulation results clearly reveal a strong dependence of the fractal dimension on the kinetics of the concurrent coagulation and sintering processes. Considering appropriate values of Df in aerosol process simulations may therefore be important in many cases.